Atypical microorganisms in children with community - Acquired pneumonia: EsSalud Grau Emergency Hospital - Period 2008 - Miranda Candelario, Javier Francisco (2012)
Objective: The objective of the present study was to determine the clinical-serological profile of atypical agent in children with community-acquired pneumonia at Emergency Hospital Grau period 2008. Material and Methods: The present study has a prospective design of cross sectional, was carried out during the year 2008, including a sample of 70 patients between 1 month to 14 years old with clinical and radiological diagnosis of community-acquired pneumonia, hospitalized at the Service of Paediatrics, Emergency Hospital Grau. They were screened by IgM ELISA for acute M. pneumoniae and C. pneumoniae infection. Results: We obtained that 31.4 % (22/70) of the children with community-acquired pneumonia presented positive serology for atypical agents, corresponding to Mycoplasma pneumoniae 7.1 % (5/70), for Chlamydia pneumoniae 17.1 % (12/70), and a mixed infection (M. pneumoniae and C. pneumoniae) in 7.1 % (5/70), we also found that infection for atypical agents increased with age (p= 0.01) thus it has a frequency of infants aged 1 months- 2 years was 14,29% preschool-aged children, 27,27% school-aged children and adolescents, 48,15%; no statistically significant difference was found between both sex (p=0,242). History of asthma was found in 54,5 % (12/22), (p=0,131). The clinical examination revealed wheezing in 72,7 % of positive serologically patient (p=0,141). About complete blood count we found a mean leukocytes count of 14,61 +-8,53 x 1000 cel/dL, Neutrophil in 77,41+-12,43% (p=0,037) and Lymphocytes in 12,59+- 7,01% (p=0,001). PCR mean of 3, 40+-2,11 UI/dL (p=0,138). Chest x-rays were classified into Interstitial infiltrations (59,09%), followed by Hyperaereation (40,91%), Lobar consolidation (40, 91%) and Atelectasis in 18,18%. Conclusions: The results of this study suggest the important role of C. Pneumoniae and M. pneumoniae, in childhood community-acquired pneumoniae in our country. The right diagnosis lead to start of specific antibiotic treatment, reducing thus the duration of hospitalization.